A Bibliometric Analysis on Urbanization Research From 1984 to 2013. Issue 3 (1st September 2015) - Pu, Bo; Qiu, Yanjun
Abstract : We performed a bibiometric analysis on urbanization research based on the 3, 058 peer-reviewed articles in the SCI and SSCI database from 1984 to 2013. Our analysis revealed document types, scientific outputs, subject categories, major journals and major authors, geographic distribution, highly cited papers and citation networks and temporal trends in keywords burst. Growth of article output has emerged since 1990, and went through two development stages. Environmental sciences, urban studies and ecology came out the most urbanization articles and Landscape and Urban Planning was the most productive journal in urbanization studies. Tothmeresz B was the most prolific author. USA was the most productive country, but Chinese Academy of Sciences was the most high-producing institution. Three streams were identified among the 65 most cited articles in the LCS historiography, and Schueler's (1994) article has the strongest bursts. A keyword analysis revealed that the "China", "city" and "globalization" are the research hotspots in the future.